Implementation of an Internal Quality Assurance System Based on Rapor Pendidikan in Sekolah Penggerak - Dini Irawati; Tedi Priatna; Qiqi Yuliati Zakiyah; Rifki Rosyad (Yayasan Azka Hafidz Maulana, 2026)
This research is motivated by the fact that most of the preparation and budgeting of quality improvement programs and activities are not fully data-based, so they are still partial and unsustainable. This is a problem that will impact other aspects, including the implementation of programs in educational units that are not measurable, partial, and unsustainable, ultimately resulting in no significant improvement in educational quality. The purpose of this study is to determine the implementation of an internal quality assurance system based on educational report cards in senior high schools. The implementation of research related to the implementation of an internal quality assurance system based on educational report cards in senior high schools, used qualitative research with descriptive study methods. The results of this study indicate that the implementation of SPMI also faces challenges. One of them is the resistance of some teachers to changes in learning approaches based on data and project literacy. The impact of the implementation of an internal quality assurance system based on educational report cards has brought significant changes to the learning process. Teachers are more active in adapting learning approaches based on critical literacy and project-based learning. Students are involved in exploratory activities such as mini-research, article presentations, and text-based group discussions. The school climate has become more positive and dialogical. Relationships between students, teachers, and management have become more open thanks to regular reflection spaces and collaborative literacy activities. Student discussion forums have become a healthy platform for criticism and appreciation of the school system.